A Comparative Pharmaceutical and Analytical Study of Shodhita Guggulu in Different Shodhana Media w.s.r. to Estimation of Guggulsterone Isomers (E&Z) - K.G Purushotham; K Shruthan; Gopakumaran K; M Harshitha; G.B Rohith Krishnan (AYUSHDHARA, 2022)
To eliminate the poisonous character and to increase the therapeutic efficacy, the texts have advocated Shodhana for Guggulu before their therapeutic application. Methodology: A comparative pharmaceutical analytical study of Shodhitha Guggulu purified by four different Shodhana methods with special reference to the comparative analytical study of Guggulsterone isomers E & Z by HPLC method. Heating and dissolving in four different Shodhana media is followed in the current study. Four types of Shodhita Guggulu got after pharmaceutical study by using four different Shodhana media. Guduchi kwatha Shodhita Guggulu (GKSG), Triphala kwatha Shodhita Guggulu (TKSG), Gomutra Shodhita Guggulu (GMSG), Nirgundi Swarasa with Haridra Choorna Shodhita Guggulu (NHSG). The essential analytical studies as per API were conducted and a comparative study was done. The yield of Shodhita guggulu was more in TKSG (79.6%) followed by (NHSG) which (71.6%), (GKSG) 68.8%, And the least yield (GMSG) Total 156g of Shodhita guggulu yielded by 62.4% o. The analytical profiles of Shuddha guggulu varied in 4 different samples. In the comparative analytical parameters of four Shodhitha guggulu by HPLC with special reference to Guggulsterone isomer E was found highest to lowest in GKSG (0.084%), NHSG (0.0697%), GMSG (0.0074%) & TKSG (0.006%) respectively. The analytical study of Guggulsterone isomer Z was found highest in both sample GKSG (0.39%) & NHSG (0.39%). And the second highest value got in GMSG (0.194%) and the least value of Guggulsterone Z was noted in TKSG (0.008%). Conclusion: Considering the active ingredient Guggulsterone isomer E; the best sample among the four different Shodhita Guggulu in the present study is Guduchi Kwatha Shodhita Guggulu. And when considering the therapeutic efficacy by Guggulsterone isomer Z; both Guduchi Kwatha Shodhita and Nirgundi Swarasa with Haridra Choorna Shodhita Guggulu are the best among the present study samples.